Investigating the nexus between strategic human resource management practices and employee engagement - Uddin, Mahi (IIUC Studies, 2022)
This study explores the relationships between strategic human resource management practices and employees' work engagement in Bangladesh's ready-made garment (RMG) industry. The study collected data through a self-administered questionnaire survey from 178 employees from 12 RMG firms located in Chittagong employing convenient sampling technique. The partial least squares technique was utilized to examine the validity and reliability of data and to test the proposed hypotheses. The findings reveal that four out of five hypotheses were accepted. Particularly, results demonstrated that recruitment and selection, performance appraisal, employee participation, and compensation directly impacted work engagement. These are essential strategic human resources management (SHRM) practices to foster employee work engagement in the Bangladeshi RMG industry. This study contributes to the SHRM-work engagement literature by providing further evidence about predictors of work engagement in the manufacturing sector in a developing economy. The study also explains the implications for theory and practice and limitations and directions for future studies. IIUC Studies Vol.18, December 2021: 9-32